Le crapouillot : magazine non conformiste. (Paris : Société d'Editions Parisiennes Associées, 1930)
Fonds Suzan Daniel (FSD)
Periodiciteit : driemaandelijks
Redactie : 3, Place de la Sorbonne, Paris
Frans
Periodiek